1991
DOI: 10.1007/bf01720677
|View full text |Cite
|
Sign up to set email alerts
|

Continuous arteriovenous haemodiafiltration in the critically ill: Influence on major nutrient balances

Abstract: The impact of continuous arteriovenous haemodiafiltration (CAVHD) on nitrogen, lipid and carbohydrate balance was studied in 9 parenterally fed critically ill patients with acute renal failure. The effects on carbohydrate delivery of varying dialysate glucose concentrations or flow rates were also investigated. The total daily nitrogen loss was a mean of 24.1 g (95% CI 20.9-27.3 g/24 h) with non-urea nitrogen losses of 7.6 g (95% CI 5.6-9.6 g/24 h). Glucose delivery was a mean 5.8 g/h with a dialysate glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 13 publications
1
38
1
Order By: Relevance
“…Moreover, although such recommendations appear reasonable from a nitrogen-balance point of view, especially given the loss of amino acids during CRRT [21,22,23,24,25,26,27], the only randomized controlled trial focusing on clinical outcomes was conducted in 1973 [28] and has little relevance to modern practice. Moreover, recent investigations have suggested that permissive underfeeding, trophic feeding, or delayed parenteral feeding may be equivalent or perhaps superior to currently recommended approaches [29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although such recommendations appear reasonable from a nitrogen-balance point of view, especially given the loss of amino acids during CRRT [21,22,23,24,25,26,27], the only randomized controlled trial focusing on clinical outcomes was conducted in 1973 [28] and has little relevance to modern practice. Moreover, recent investigations have suggested that permissive underfeeding, trophic feeding, or delayed parenteral feeding may be equivalent or perhaps superior to currently recommended approaches [29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Bellomo et a1. 43 , a group of 24 CAVHDF/CVVHDF patients with a medium Apache II score of 24 to 29 demonstrated a significantly lower mortality rate of 53% compared with the IHD group (87%). These results were confirmed in a subsequent analysis in 234 ICU patients, in which continuously treated patients with Apache II score of 19 to 29 again had a significantly lower mortality rate than ARF patients treated with IHD or peritoneal dialysis (PD) 57 .…”
Section: Influence Of Crrt On Outcome Of Arf Patientsmentioning
confidence: 86%
“…Bellomo et al 43 demonstrated that 90% of patients received the prescribed nutrition during CRRT, as oposed to only 54% of patients during IHD. A subsequent study showed that 91% of the patients were able to receive more than 1.5 g protein/kg/d during CRRT, oposite to IHD and peritoneal dialysis treated ARF patients who received only up to 1.0 and 0.8 g/kg/d, respectively.…”
Section: Unlimited Alimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition the¯uid retention referred to earlier can cause problems with parenteral feeding and this may have to be limited because of the dangers of¯uid overload on lung function and gas exchange . Increasingly however, as experience is gained with haemo®ltration, excess uid is being actively removed in order to allow adequate nutrient support (Rodriguez et al, 1992;Bellomo et al, 1991).…”
Section: The Delivery Of Nutritional Support In the Critically Illmentioning
confidence: 99%